Comparative study of Chemical Pathology sample collection tubes at the largest hospital in South Africa: Comparison between BarricorTM and serum separator tubes - Khoza, Siyabonga; Ford , Sarah; Buthelezi, Ernest; Tanyanyiwa, Donald (Journal of Medical Biochemistry, 2021)
Background: BarricorTM lithium heparin plasma tubes are new blood tubes that have been introduced to overcome the effects of gel in serum separator tubes (SST) and the shortcomings of standard lithium heparin plasma. We aimed to evaluate BarricorTM tubes as an alternative to serum separator tubes and compare the stability between the tubes. Methods: Forty-four paired samples were collected using both BarricorTM and SST. We compared five analytes at baseline (<6h) and after every 24h using the Passing-Bablok and Bland-Altman plots. Aspartate aminotransferase (AST), potassium (K), phosphate (PO4), lactate dehydrogenase (LDH), and creatinine were analysed in both tubes. We calculated the percentage difference for each analyte between the baseline and time intervals to assess analyte stability. The percentage difference was compared to the desirable specification for bias and reference change value (RCV). Results: All analytes were comparable at baseline. Statistical differences (p<0.001) became evident after 24h. PO4, K, and creatinine had a mean difference that exceeded the desirable specification for bias (-9.59%, -9.35%, and -4.59%, respectively). Potassium was stable up to 24h in both tubes. LDH showed better stability in SST (144h vs. 96h). PO4 concentrations were more stable in both tubes with the SST (96h vs. 72h). Creatinine and AST had the longest stability in both tubes compared to other analytes (144h). Conclusions: Data demonstrated variability and similarities in analyte concentrations and stability, respectively in both tubes